Patient reported side-effects of prednisone and methotrexate in a real-world sarcoidosis population. (21st September 2021) - Kahlmann, Vivienne; Moor, Catharina C; Veltkamp, Marcel; Wijsenbeek, Marlies S
Currently prednisone is the first-line pharmacological treatment option for pulmonary sarcoidosis. Methotrexate is used as second-line therapy and seems to have fewer side-effects. No prospective comparative studies of first-line treatment with methotrexate exist. In this study, we evaluated patient reported presence and bothersomeness of side-effects of prednisone and methotrexate in a sarcoidosis population to guide the design of a larger prospective study. During a yearly patient information meeting 67 patients completed a questionnaire on medication use; 11 patients never used prednisone or methotrexate and were excluded from further analysis. Of the remaining 56 patients, 89% used prednisone and 70% methotrexate (present or former). Significantly more side-effects were reported for prednisone than for methotrexate, 78% versus 49% ( p = 0.006). In conclusion, methotrexate seems to have fewer and less bothersome side-effects than prednisone. These findings need to be confirmed in a prospective study.